EVALUATION OF THE ROLE OF CONTROL SYSTEMS ON FINANCIAL MANAGEMENT IN PUBLIC SECONDARY SCHOOLS: A CASE OF KAKAMEGA CENTRAL DISTRICT. - ATIENO, OMONDI MARGARET; SANGORO, OSCAR ONYANGO; ATIENO, JOSEPH ODUOR; ODONGO, TOBIAS OCHIENG; RONO, DR LUCY (IJRDO - Journal of Applied Management Science, 2015)
Governments around the world recognize the importance of education for personal andeconomic development and they invest huge sums of money on education annually. Thehuge investment on education by the government, parents and other stakeholders thereforecalls for proper use and control of these resources. The GOK has put measures to ensureeffective management of funds in schools like sending auditors to schools every year, insisting on public secondary schools keeping proper books of accounts, authorization ofany payments by the BOG and non cash payment of tenders among other measures.Despite the control measures put in place some funds still get to wrong hands due tomisuse and misappropriation. It is on the basis of the misappropriations that the studyseeks to evaluate the role of control systems on financial management of public secondaryschools in Kenya. The study will be based on Agency Theory and Reliability Model. Thestudy will be guided by the Independent Variable - Control Systems, the DependentVariable - Financial Management and the Moderating Variable- School Factors.Descriptive survey research design will be used. Census technique will be used to getinformation from principals’ bursars and other 8 members of the tendering committee ineach school because they all hold key information and to avoid bias. The target populationwill be 190.This will consist of 19 principals, 19 bursars and 152 members of the tendercommittee from 19 public secondary schools in Kakamega central. Primary data will becollected by use of questionnaires and structured interviews, while secondary data will becollected through document analysis of financial records. Reliability of the researchinstruments will be tested through split half method. Validity will be tested through expertanalysis of the research instruments and a pretest of the questionnaires in Kakamega southdistrict. Both quantitative and quantitative data will be collected. The collected data willbe coded and classified then entered into the computer to obtain descriptive statistics suchas; frequencies, percentages, mean median, mode and variance by use of a tool such asSPSS. The data will then be presented inform of in form of tables, charts and graphs. Thestudy may add to the existing literature on control systems, it may be used by policymakers to improve financial management in public secondary schools and may also helpmanagers like principals and bursars to improve on their financial management practices.